Seasonal Influence on Efficacy of Ovsynch, Heatsynch and Triu-B Protocols in Terms of Estrus Response, Conception Rate and Biochemical Profile in Postpartum Anoestrus Buffaloes
This study was undertaken on 48 postpartum (>90 days) anoestrus buffaloes each in winter and summer seasons with the object to know the seasonal influence on efficacy of three estrus induction/ synchronization protocols towards fertility response and blood biochemical profiles. Twelve buffaloes each in treatment group I, II and Ill were subjected to Ovsynch, Heatsynch and Triu-B hormone protocols, respectively, while group IV served as untreated control. The estrus induction response varied from 75.00 to 83.33% during summer and 83.33 to 91 .66% during winter season with these protocols. The conception rates obtained at induced estrus and overall of 3 cycles in anoestrus buffaloes were comparatively lower under all three protocols during summer than winter season (16.27 vs 41.67 & 25.00 vs 58.33% for Ovsynch; 16.27 vs 25.00 &25.00 vs 50.00% for Heatsynch, and 16.27 vs 41 .67 & 33.33 vs 58.33%, respectively), and obviously higher than control group (overall CR 8.33 & 25.00%